La participation des enfants à l’école sous le prisme des droits de l’enfant - Maude Louviot (Éducation et Socialisation)
Based on the theory developed in the field of children’s rights research, this article proposes to reflect conceptually pupil participation in school in a broad sense. By adopting a meta perspective on different varieties of participation, we define an effective participatory approach and underline the link between child participation in school and the implementation of the Convention on the rights of the child. Indeed, if participatory intentions are multiplying in practices and official prescriptions (democratic debates, philosophical discussions, student councils, cooperative practices, etc.) we argue that not all forms of pupils’ participation are equal and that some approaches are more effective than others.